Diagnosis of occlusal enamel caries using near-infrared light transillumination - A/Prof NEKKANTI SRIDHAR; Dr Liz Mary Gerald (Elsevier, 2023)
Aim or Purpose: The purpose of this in- vitro study is to evaluate the ability of DIAGNOcam™ to detect occlusal caries at an early stage and to compare it with ICDAS II criteria, DIAGNOdent™, and digital radiography using histological validation as a reference standard. Materials and Methods: Thirty-five primary molars with early occlusal enamel caries were first examined visually using ICDAS II criteria, DIAGNOdent™, VistaScan™ and DIAGNOcam™. Sectioning of the teeth was done for histological validation and the presence of caries was evaluated using Downer's criteria. The Chi- square test was used for inferential statistics. Individual correlation of Visual examination, DIAGNOdent™, VistaScan™ and DIAGNOcam™ done with histology. Correlation of Visual examination, DIAGNOdent™ and VistaScan™ done with DIAGNOcam™. Sensitivity analysis was done to calculate sensitivity, specificity, positive predictive value, negative predictive value, accuracy and area under the receiver operating characteristic (ROC) curves based on the histological results. Results: There was a statistically significant correlation between visual examination, VistaScan™, DIAGNOdent™, and DIAGNOcam™ with histology. Also statistically significant was the correlation between visual examination, VistaScan™, and DIAGNOdent™ with DIAGNOcam™ Conclusions: In diagnosing early occlusal caries, DIAGNOcam™ has demonstrated results superior to the histological gold standard. NILT has proven to be a valuable tool for clinical practice and can be utilized as a supplement to visual examination.